SCENES FROM HAITIAN EXPERIENCES, WITH YANICK LAHENS: ESSAY OF A TRANSLATION - Deangeli, Maria Angelica; Furquim, Juliana (Revista de Letras, 2023)
The principal objective of this article is to present the commented translation, from French into Brazilian Portuguese, of the short story Une histoire américaine, extracted from the book La petite corruption (1999), by the Haitian writer Yanick Lahens. To do so, it commences, on the one hand, with the theoretical research on translation and on annotated translation in an academic context; and, on the other hand, the Haitian universe in which the short story is inserted. Thus, in the context of translation, Antoine Berman's studies form the basis, mainly his work A tradução e a letra ou o albergue do longínquo (2007). Regarding the commented translation genre, reference is made to the research by Torres (2017) and Sardin (2007), in which the authors address the problem of annotated translation in an academic context and point out the intrinsic relationship between annotation and translation. Mittmann's (2003) work regarding translation notes from a discursive perspective is also mentioned. The works of Cadely (2016) and Cothière (2017) are used to investigate the particularities of Yanick Lahens' writing in French and to address the historical and cultural issues underlying the narrative. Keywords: French language; annotated translation; Yanick Lahens.